Yurisprudensi Islam dan Fikih Sosial: Dampaknya terhadap Kesejahteraan Masyarakat di Indonesia: Islamic Jurisprudence and Social Fiqh: Impacts on Community Welfare in Indonesia - Abdain; Rahmawati; Takdir (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Islamic jurisprudence remains a central foundation for Muslim social life, yet its practical relevance to contemporary welfare challenges requires further academic clarification. In Indonesia, where Islamic values interact with diverse cultural, institutional, and policy contexts, social fiqh has emerged as an important framework for translating Islamic legal principles into socially responsive practices. However, previous studies have often discussed Islamic jurisprudence and welfare separately, leaving a gap in explaining how social fiqh bridges normative legal theory and practical community welfare outcomes. This study investigates the relationship between Islamic jurisprudence and social fiqh by addressing the question of how Islamic legal principles are interpreted through social fiqh and how this interpretation contributes to community welfare in Indonesia. The study employed a qualitative library research design by reviewing secondary sources, including peer reviewed journal articles, open access academic publications, books, book chapters, and institutional reports. The selected literature was analyzed through qualitative content analysis and thematic analysis. The findings show that maqasid al shariah, maslahah, and adaptive legal reasoning are dominant frameworks in welfare oriented Islamic jurisprudence. Social fiqh is applied through zakat management, waqf development, Islamic social finance, religious leadership, and community based welfare programs. These findings imply that Islamic jurisprudence can serve as a dynamic theoretical and practical foundation for strengthening community welfare when supported by contextual interpretation, institutional accountability, and community participation.